Changed Rumen Fermentation, Blood Parameters, and Microbial Population in Fattening Steers Receiving a High Concentrate Diet with Saccharomyces cerevisiae Improve Growth Performance - Kampanat Phesatcha; Burarat Phesatcha; Krittika Chunwijitra; Metha Wanapat; Anusorn Cherdthong (Veterinary Sciences, 2021)
The effect of dry yeast (DY) (Saccharomyces cerevisiae) supplementation in a high-concentrate diet was evaluated for rumen fermentation, blood parameters, microbial populations, and growth performance in fattening steers. Sixteen crossbred steers (Charolais x American Brahman) at 375 ± 25 kg live weight were divided into four groups that received DY supplementation at 0, 5, 10, and 15 g/hd/d using a completely randomized block design. Basal diets were fed as a total mixed ration (roughage to concentrate ratio of 30:70). Results showed that supplementation with DY improved dry matter (DM) intake and digestibility of organic matter (OM), neutral detergent fiber (NDF), and acid detergent fiber (ADF) (p < 0.05), but DM and crude protein (CP) were similar among treatments (p > 0.05). Ruminal pH (>6.0) of fattening steer remained stable (p > 0.05), and pH was maintained at or above 6.0 with DY. The concentration of propionic acid (C3) increased (p < 0.05) with 10 and 15 g/hd/d DY supplementation, while acetic acid (C2) and butyric acid (C4) decreased. Methane (CH4) production in the rumen decreased as DY increased (p < 0.05). Fibrobacter succinogenes and Ruminococcus flavefaciens populations increased (p < 0.05), whereas protozoal and methanogen populations decreased with DY addition at 10 and 15 g/hd/d, while Ruminococcus albus did not change (p > 0.05) among the treatments. Adding DY at 10 and 15 g/hd/d improved growth performance. Thus, the addition of DY to fattening steers with a high concentrate diet improved feed intake, nutrient digestibility, rumen ecology, and growth performance, while mitigating ruminal methane production.